Release of heavy metals during long-term land application of sewage sludge compost: Percolation leaching tests with repeated additions of compost. (February 2017) - Fang, Wen; Delapp, Rossane C.; Kosson, David S.; van der Sloot, Hans A.; Liu, Jianguo
Abstract: Leaching assessment procedures have been used to determine the leachability of heavy metals as input for evaluating the risk from sewage sludge compost land application. However, relatively little attention has been paid to understanding leaching from soils with repeated application of sewage sludge compost with elevated levels of heavy metals. In this paper, leaching assessment is extended to evaluate the potential leaching of heavy metals during repetitive application of composted sewage sludge to soils. Four cycling of compost additions and percolation leaching were conducted to investigate how leaching behavior of heavy metals changed with repeated additions of compost. Results showed that repetitive additions of compost to soil significantly increased the content of organic matter, which favored the formation of reducing condition due to improved microbial activities and oxygen consumption. Establishment of reducing conditions can enhance the leaching concentrations of As by approximately 1 order of magnitude, especially for the soil rich in organic matter. For Cd, Cr, Cu, and Pb, repeated additions of compost will cause accumulation in total contents but not enhancement in leaching concentrations. The infiltration following compost additions will leach out the mobile fraction and the residual fraction might not release in the next cycling of compost addition and infiltration. The cumulative release of Cd, Cr, Cu, and Pb accounted for less than 5% of the total contents during four times of compost applications. Highlights: Leaching of heavy metals during repetitive land application of SSC was evaluated. Percolation and pH-dependent leaching test were used to understand the leaching behavior. Repeated additions of SSC favored the formation of reducing condition. Establishment of reducing conditions can enhance the release of accumulated As.